2017
DOI: 10.21037/jgo.2017.06.15
|View full text |Cite
|
Sign up to set email alerts
|

Radiation generates an abscopal response and complete resolution of metastatic squamous cell carcinoma of the anal canal: a case report

Abstract: Abstract:The abscopal effect is a rare phenomenon in the setting of radiation therapy (RT) for metastatic cancer where tumor regression occurs distant from the site of treatment. A proposed mechanism of the abscopal effect is the activation of a systemic antitumor immune response by localized RT. We report the first case, to our knowledge, of the abscopal effect in squamous carcinoma of the anal canal with metastases to pelvic lymph nodes, liver and bone. After palliative RT to the pelvis with sensitizing chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…More specifically, abscopal responses were observed in the lymph nodes downstream of the treated site in both patients. Joe et al [61] reported the first case of the abscopal effect of radiation therapy in squamous carcinoma of the anus with metastases to pelvic lymph nodes, liver, and bone. In this case, the patient had an abscopal response after treatment with palliative radiation therapy to the pelvis.…”
Section: Abscopal Effects In Other Solid Tumorsmentioning
confidence: 99%
“…More specifically, abscopal responses were observed in the lymph nodes downstream of the treated site in both patients. Joe et al [61] reported the first case of the abscopal effect of radiation therapy in squamous carcinoma of the anus with metastases to pelvic lymph nodes, liver, and bone. In this case, the patient had an abscopal response after treatment with palliative radiation therapy to the pelvis.…”
Section: Abscopal Effects In Other Solid Tumorsmentioning
confidence: 99%
“…Elevated SCC Ag represents RT-resistant tumors whereas a reduction in its levels predicts a positive tumor response [215]. In the case of AbE, the SCC Ag levels also decrease due to irradiation and the following systemic response [31].…”
Section: Tumor Markersmentioning
confidence: 99%
“…Immunohistochemical staining for CD163, CD3, CD4, and CD8 showed heterogeneity of cell distribution. Some tumor regions were densely infiltrated with lymphocytes, including CD8+ and CD4+ T cells, suggesting a profuse immune response [31].…”
Section: Tumor-infiltrating Lymphocytesmentioning
confidence: 99%
“…Joe et al reported the case of the abscopal effect in squamous carcinoma of the anal canal, with metastases to the pelvic LN, liver, and bone [79]. After palliative RT to the pelvis with sensitizing chemotherapy but without immunotherapy, complete response was observed not only in the primary tumor but also in the bone and multiple liver metastases at 4 months after treatment.…”
Section: Biomarkers In Tumorsmentioning
confidence: 99%